2018
DOI: 10.1093/bioinformatics/bty707
|View full text |Cite
|
Sign up to set email alerts
|

admetSAR 2.0: web-service for prediction and optimization of chemical ADMET properties

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
522
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 962 publications
(525 citation statements)
references
References 13 publications
0
522
0
3
Order By: Relevance
“…A potential solution is to predict candidate pharmacogenes according to the chemical structure of a new drug by the artificial intelligence and machine learning algorithm [21,22] . Then related molecular biological studies can be conducted to validate these candidate pharmacogenes rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…A potential solution is to predict candidate pharmacogenes according to the chemical structure of a new drug by the artificial intelligence and machine learning algorithm [21,22] . Then related molecular biological studies can be conducted to validate these candidate pharmacogenes rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Although actein differs in the structure of these mental‐treated drugs, it is found that they are similar in expression by the method of biclustering, which indicates that there is a similar activity between actein and these drugs. And the ADMET‐associated (Absorption, distribution, metabolism, excretion, and toxicity) properties of actein are predicted by admetSAR, a web platform developed as a comprehensive source and free tool for the prediction of chemical ADMET properties . According to the predicted values, most of the properties of actein basically meet Lipinski's principle, which indicates that it is suitable as a candidate drug.…”
Section: Resultsmentioning
confidence: 99%
“…And the ADMETassociated (Absorption, distribution, metabolism, excretion, and toxicity) properties of actein are predicted by admetSAR, a web platform developed as a comprehensive source and free tool for the prediction of chemical ADMET properties. [13] According to the predicted values, most of the properties of actein basically meet Lipinski's principle, which indicates that it is suitable as a candidate drug. (As shown in Table 3).…”
Section: Similarity Analysis Of Module Regulationmentioning
confidence: 95%
“…Absorption, distribution, metabolism, excretion, and toxicity (ADMET) screening of ligands helps to determine their absorption properties, toxicity, and drug-likeness. Ligand molecules saved in .smiles format and selected drugs [29,30].…”
Section: Admet and Toxicity Predictionmentioning
confidence: 99%